Autophagy Inhibition Improves Sunitinib Efficacy in Pancreatic Neuroendocrine Tumors via a Lysosome-dependent Mechanism - Wiedmer, Tabea; Blank, Annika; Pantasis, Sophia; Normand, Lea; Bill, Ruben; Krebs, Philippe; Tschan, Mario P; Marinoni, Ilaria; Perren, Aurel (Molecular cancer therapeutics, 2017)
Increasing the efficacy of approved systemic treatments in metastasized pancreatic neuroendocrine tumors (PanNET) is an unmet medical need. The antiangiogenic tyrosine kinase inhibitor sunitinib is approved for PanNET treatment. In addition, sunitinib is a lysosomotropic drug and such drugs can induce lysosomal membrane permeabilization as well as autophagy. We investigated sunitinib-induced autophagy as a possible mechanism of PanNET therapy resistance. Sunitinib accumulated in lysosomes and induced autophagy in PanNET cell lines. Adding the autophagy inhibitor chloroquine reduced cell viability in cell lines and in primary cells isolated from PanNET patients. The same treatment combination reduced tumor burden in the Rip1Tag2 transgenic PanNET mouse model. The combination of sunitinib and chloroquine reduced recovery and induced apoptosis , whereas single treatments did not. Knockdown of key autophagy proteins in combination with sunitinib showed similar effect as chloroquine. Sunitinib also induced lysosomal membrane permeabilization, which further increased in the presence of chloroquine or knockdown of lysosome-associated membrane protein (LAMP2). Both combinations led to cell death. Our data indicate that chloroquine increases sunitinib efficacy in PanNET treatment via autophagy inhibition and lysosomal membrane permeabilization. We suggest that adding chloroquine to sunitinib treatment will increase efficacy of PanNET treatment and that such patients should be included in respective ongoing clinical trials. .